Talent Production in Interaction: Performance Appraisal Interviews in Talent Selection Camps - Kilger, Magnus; Jonsson, Rickard (Communication and sport, 2017)
In sports, there is an extensive interest in identifying and selecting talented children in order to develop elite adult athletes. The process of selecting and screening talents involves not only physical and technical skills but also efforts to find adequate personality traits. Therefore, different types of performance appraisal interviews (PAIs) are becoming increasingly common within the field. Departing from fieldwork in two selection camps for Swedish youth national teams in soccer and hockey, we will take a closer look at the PAIs employed during these camps. This article takes on a narrative approach, emphasizing PAI as a narrative genre and a framework for a specific form of interaction. Our findings show how eligibility is performed in interaction through following three practices: (i) showcasing gratitude without tipping into flattery, (ii) using temporality as a way of displaying developmental potential, and (iii) adopting the role of the self-reflecting subject. This genre of interviews not only produces certain practices but also preferred subject positions and narratives. The PAI is thus a narrative genre where the players are encouraged to perform talent in order to appear selectable.